Influence of paclobutrazol on growth performance, photosynthetic pigments, and antioxidant efficiency of Pathumthani 1 rice seedlings grown under salt stress - Bundit Khunpon (2018)
© 2017, Science Society of Thailand under Royal Patronage. All rights reserved. The ability of paclobutrazol to ameliorate salinity stress, growth performance, photosynthetic pigment, and antioxidant efficiency was studied in indica rice cv. Pathumthani 1. Fourteen-day-old rice seedlings were pretreated with 15 mg/l paclobutrazol by foliar spray and subsequently exposed to salt stress (150 mM NaCl) for 12 days. Salt stress decreased growth characters including fresh weight, dry weight, shoot length, root length, shoot fresh weight, shoot dry weight, root fresh weight, and root dry weight. It also reduced the photosynthetic pigments chlorophyll a, chlorophyll b, total chlorophyll, and total carotenoids. In addition, salinity stress decreased the total antioxidant capacity as determined by 2,2-diphenyl-1-picrylhydrazyl, 3-ethylbenzothiazoline-6-sulphonic acid, and ferric-reducing antioxidant power assays and reduced the activities of the antioxidant enzymes, peroxidase and polyphenol oxidase, in both leaves and roots. Seedling growth retardation and pigment degradation were positively correlated with the reduction of antioxidant efficiency under salt stress. Paclobutrazol pretreatment improved growth, pigment production, and antioxidant efficiency in salt -stressed rice seedlings. These results indicate that paclobutrazol plays an important role in ameliorating the impact of salinity stress on Pathumthani 1 rice seedlings.